2021
DOI: 10.1097/md.0000000000027720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cognitive behavioral therapy on anxiety and depression in patients with psoriasis

Abstract: Background: Psoriasis can lead to higher social and psychological burden, and its occurrence is related to psychological disturbance. At present, there are many clinical trials on cognitive behavior therapy for depression and anxiety in patients with psoriasis. However, the results of studies vary greatly due to the different time and content of the intervention, and the curative effect is still controversial. Therefore, the purpose of this study was to explore the effect of cognitive behavior therapy on anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Psoriasis is a chronic condition characterized by extensive skin lesions and a signi cant amount of desquamation, which aggravate patients' psychological symptoms, forming a vicious circle and resulting in severe and long-lasting disease. Controlling bad emotions and improving mental and psychological states have certain therapeutic effects, and combined psychotherapy is better than single therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic condition characterized by extensive skin lesions and a signi cant amount of desquamation, which aggravate patients' psychological symptoms, forming a vicious circle and resulting in severe and long-lasting disease. Controlling bad emotions and improving mental and psychological states have certain therapeutic effects, and combined psychotherapy is better than single therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Even though all these coping mechanisms are beneficial and appreciated by the patient, psychological therapy remains the best treatment for a patient in distress and it may be good to be given in patients with psoriasis-related depression and anxiety in the form of cognitive behavioural therapy [ 34 ].…”
Section: A Proposal For Alternative Coping Mechanismsmentioning
confidence: 99%
“…Several international studies have shown that CBT can reduce sadness, anxiety, and other negative emotions. However, this has not been proven through a comprehensive examination (Tan et al, 2021). The purpose of study are; (1) what are the other conditions related to psoriasis?, and…”
Section: Introductionmentioning
confidence: 99%